PENGARUH SECTIO CAESAREA METODE ERACS TERHADAP MOBILISASI DINI PADA IBU BERSALIN DI RUMAH SAKIT HERMINA BALIKPAPAN - Hariyani, Tintin; Anggun Irmadani, Richa; Eko Suparni, Ita (Prosiding SPIKesNas : Seminar Publikasi Ilmiah Kesehatan Nasional, 2024)
Sectio caesarea is the birth of a fetus through an incision made in the abdominal wall and uterus, after the delivery procedure, many mothers complain about their condition, ranging from post-operative pain, difficulty in mobilizing and fulfilling personal needs, and the demands of mothers in caring for their babies, therefore, it is hoped that there will be innovations that can help the recovery process of post-cesarean section patients so that they can recover faster, Currently, the CS method of delivery is known with the concept of ERACS (Enhanced Recovery After Cesarean Section) which is a more comfortable operation process because there is less pain and the recovery process after surgery is faster than conventional CS. This study aims to determine the effect of sectio caesarea eracs method on early mobilization in mothers giving birth at Hermina Hospital Balikpapan. The research method used is analytical observational using a cross-sectional approach, this study is a type of research that only measures observation data of research subjects once at one time, the type of sample used is Total Sampling, data collection using observation sheets, with analytical tests using the Wilcoxon Sigh Rank Test. The results of the study obtained are the effect of Sectio Caesaria ERACS Method on Early Mobilization in Women Giving Birth at Hermina Hospital Balikpapan, it can be seen that the results of the statistical test value Asym. Si.g (2-tailed) is 0.096 which means p <0.096 (p = 0.05), which means Ha is accepted and Ho is rejected, so it can be concluded that there is a significant effect of Sectio Caesaria ERACS Method on Early Mobilization in Women Giving Birth at Hermina Hospital. From the results of the study, it was concluded that the effect of Sectio Caesaria ERACS Method on Early Mobilization in Women Giving Birth at Hermina Hospital Balikpapan is effective in the speed of patients to carry out early mobilization and shorten the length of care.